Adherence to human lung microvascular endothelial cells (HMVEC-L) of Plasmodium vivax isolates from Colombia (2013)
ABSTARCT: For years Plasmodium vivax has been considered the cause of benign malaria. Nevertheless, it has been observed that this parasite can produce a severe disease comparable to Plasmodium falciparum. It has been suggested that some physiopathogenic processes might be shared by these two species, such as cytoadherence. Recently, it has been demonstrated that P. vivax-infected erythrocytes (Pv-iEs) have the capacity to adhere to endothelial cells, in which intercellular adhesion molecule-1 (ICAM-1) seems to be involved in this process.